Prevention Efforts of Sexual Violence in Students at SMPN 1 Jatinangor - Nina Sumarni; Udin Rosidin; Iceu Amira DA; Hendrawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The increase cases of sexual violence, especially against teenagers, is a serious issue that requires immediate attention and action. The impact of sexual violence on teenagers can be very damaging, both physically and psychologically. To overcome this problem, a holistic approach is needed, one of which is by education. This educational activity aims to provide teenagers with a better understanding of the signs of sexual violence, and how to report it. It is hoped that this education will trigger awareness and change behavior so that teenagers can protect themselves.This method of socializing educational activities can be carried out through lectures and questions and answers at schools or youth communities. An interactive and informative approach is very important to make participants actively involved in the learning process. The number of participants who attended this activity was 31 students, both male and female. The results of this educational activity were measured by evaluating participants' knowledge before and after the education, the previous score was only 62 and after the education it increased to 84, where there was an increase in knowledge of 22 points after the activity.top of form teenagers